Black Stink Bug Proxys punctulatus (Palisot) (Insecta: Hemiptera: Pentatomidae) - Celina Gomez; Russell F. Mizell, III (EDIS)
EENY-432, a 3-page illustrated fact sheet by Celina Gomez and Russell F. Mizell III, is part of the Featured Creatures collection. It describes this stink bug with broad geographical range in the Americas — distribution, description, life cycle and biology, hosts, and damage. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.